2017
DOI: 10.1002/hed.24906
|View full text |Cite
|
Sign up to set email alerts
|

Oropharynx‐directed ipsilateral irradiation for p16‐positive squamous cell carcinoma involving the cervical lymph nodes of unknown primary origin

Abstract: Oropharynx-directed, ipsilateral radiation results in disease control that compares favorably with historical controls treated by comprehensive mucosal and bilateral neck radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…EMI to the oropharynx will likely play an important role in optimizing locoregional control and alleviating acute and late toxicity by sparing the aerodigestive tract. [24][25][26] Regarding radiation dose, a dose of 60Gy were used in our study for the consideration that the high-risk mucosal regions were hiding small cancers. IMRT techniques could spare patients from extensive toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…EMI to the oropharynx will likely play an important role in optimizing locoregional control and alleviating acute and late toxicity by sparing the aerodigestive tract. [24][25][26] Regarding radiation dose, a dose of 60Gy were used in our study for the consideration that the high-risk mucosal regions were hiding small cancers. IMRT techniques could spare patients from extensive toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 Four studies using unilateral cervical neck radiation in a subset of patients with HPV/p16-positive SCCUP yielded different results in terms of treatment outcomes ranging from inferior to equal or superior to bilateral radiation. 81 The use of long-term gastrostomy tube is rare with very few stenosis and stricture complications. 81 The use of long-term gastrostomy tube is rare with very few stenosis and stricture complications.…”
Section: Radiation With or Without Concomitant Chemotherapymentioning
confidence: 99%
“…23,54,68,69 Ipsilateral radiotherapy seems well tolerated with acceptable toxicity, which includes dysgeusia, salivary alteration, and skin erythema that reversed after symptomatic treatment. 23,81 Ninety percent of patients rated their health-related quality of life as very good. 23,81 Ninety percent of patients rated their health-related quality of life as very good.…”
Section: Radiation With or Without Concomitant Chemotherapymentioning
confidence: 99%
“…Efforts to de‐intensify therapy have resulted in studies of limited pharyngeal axis radiation. Chen et al reported 2‐year PFS of 87% in p16+ patients treated with oropharynx directed ipsilateral irradiation . Similarly, Hu et al showed a 5‐year regional control of 90% with an oropharynx‐directed radiation approach .…”
Section: Discussionmentioning
confidence: 95%
“…The decision to treat unilateral or bilateral necks in patients with HNCUP remains controversial; however, studies have shown decreased toxicity and improved patient‐reported outcomes for patients treated with unilateral neck treatment . Chen et al showed that a treatment approach targeting the unilateral neck can be used in well‐selected patients with p16‐positive disease . Tiong et al also found no contralateral neck recurrences in patients with p16‐positive HNCUP .…”
Section: Discussionmentioning
confidence: 99%